The Ferguson rifle - L'Amour, Louis, 1908-1988 (Bantam, 1996)
Stripped of all he values in life, Ronan Chantry takes up his prized Ferguson rifle and heads west--into an unknown land and an uncertain future. For an educated man, Chantry is surprisingly tough. For a civilized man, he is unexpectedly dangerous. But even he can't know the true extent of his courage until he draws the fire of a man who will do anything--kill anyone--for the glitter of gold.